Determination of the frequency of Vibrio parahaemolyticus and other halophilic vibrios in fresh prepared foods and processed marine products - Vilcapoma, Amabilia (1992)
This work was carried out in 1988 during summer and autumn seasons 122 samples were tested; 88 from frozen fish, 40 from "cebiche" marketed in Lima. To processing and to isolate the halophilic vibri'On it was followed the suggestion of FDA (1985) characterization of ,the isolates were done on morphological and cultural characteristics and biochemical tests 57 presumptive strains were isolated 42 from frozen fish and 15 from "cebiches", 5 strains Were identified as Vibrio parahaemolyticus (8.8%) and 14 strains like Vibrio aIginolyticus (24.6'0). 38 strains were characterized as Vibrio sp. (66.6%).